The Impact of Treadmill Retro Walking on Hamstring Flexibility and Speed in Distance Runners - Anisha, Nallasamy; Lokesh, Arumugam; Siti Noorhaslina, Mohd Zaidi; Lau, Pui Yee; Vinosh Kumar, Purushothaman (INTI International University, 2024)
Background: Distance runners frequently encounter constraints in terms of hamstring flexibility and running speed improvement. It is possible that existing training approaches may not sufficiently address these concerns. Analyzing the effect of retro-walking on a treadmill may provide valuable insights into an innovative strategy for enhancing hamstring flexibility and speed in distance runners. Objective: The study aims to investigate the effect of retro-walking on a treadmill on hamstring flexibility and speed in distance runners. Methodology: A total of 30 male distance runners were chosen for this quasi-experimental study. The hamstring flexibility and speed were evaluated by conducting a sit-and-reach test and a 35-meter sprint test before and after the intervention. The research intervention was administered 3 days a week over a duration of 12 weeks. The pre- and post-mean difference within the group was analyzed using a paired t-test. Result: The result showed that there was a significant improvement (mean±SD, p<0.05) in hamstring flexibility and speed within the group. Conclusion: In conclusion, incorporating retro walk into the training protocol may improve the hamstring flexibility and speed in distance runners.